Jared Diamond. Sociedades comparadas. Un pequeño libro sobre grandes temas. Barcelona, Debate, 2016, 192 págs., ISBN: 978-84-9992-558-5. - Fernández-de-Pinedo, Nadia (Investigaciones de Historia Económica, 2019)
Sin resumen